Development of bookshelf one Malaysia concept - Rashid, Mohamad Roshafizi; Zakaria, Mohd Aiman; Che Abd Manan, Ahmad Aiman (2012)
This project was including by final semester students of diploma in course of wood industry. The objective of this study is to produce a project that we have learned it before in past semester, so the student must do a thesis project to show the input or skill of their study in this course. The total cost of making this bookshelf was RM524.80 in total. From the survey that has been done, the result was the acceptable is more than to unacceptable on the material used, design style, creativity in made this bookshelf. Therefore, this study has been developed bookshelf one Malaysia concept which designed based on the wanted of unity.